An innovative infection method for the accumulation of viral nanoparticles in Nicotiana benthamiana - Ljumović, Kristina; Rosa, Anthony; Raneri, Alessia; Ballottari, Matteo; Avesani, Linda; Betterle, Nico (Frontiers in Plant Science, 2025)
Tomato Bushy Stunt Virus (TBSV) naturally infects tomato plants, although it can also infect other plant species, such as Nicotiana benthamiana, a known model system in plant molecular farming. In the presented work, a novel system for TBSV infection of Nicotiana benthamiana plants, designed to produce nanomaterials, was developed and optimized based on a simple foliar spray, without the use of surfactants. Up to now, the standard procedures for the viral infection have been syringe or vacuum infiltration, which are a time-consuming manual procedure or requiring expensive machinery, respectively. The spraying method was chosen because it could be implemented in industrial conditions, such as vertical farms, where spraying systems are already present or can be easily installed at a low cost. In this work, as a proof of concept, a wild type and a modified version of TBSV construct, which generated a viral nanoparticle (VNP) exposing a small 12 aa-domain Liprin alpha 1 protein (Lip1) on each capsid protein, were successfully expressed in Nicotiana benthamiana plants. Specifically, VNP displaying Lip1 is a candidate for the treatment of rheumatoid arthritis. After 7 days of incubation, signs of viral infection were visible in the infected plants, while prolonged incubation time to 8 days significantly increased the accumulation of VNPs. The infection method described here offers straightforwardness and scalability of plant molecular farming, representing an efficient solution for the complexity of the conventional infection process.